Strengthening Mental Health and Spiritual Survival during the COVID-19 pandemic - Yuliana Yuliana (Pusat Unggulan Ipteks Javanologi Universitas Sebelas Maret, 2023)
The COVID-19 pandemic brings significant threats to physical and mental health. Sometimes, mental health is forgotten. However, it is a crucial fact. Less is known about the temporary changes of mental health conditions due to the COVID-19 pandemic. This paper aims to describe the mental problems during the COVID-19 pandemic and how to strengthen the mental health and spiritual survival during the COVID-19 pandemic. This paper is a literature review. The literature was selected from PubMed and Google Scholar. The keywords were COVID-19, mental, spiritual, strengthening. To strengthen mental health, it needs support and strategy. Otherwise, the immune system will be decreased and the coronavirus will be easily infected the body. Sleep disorders, anxiety, depression, and suicide have increased lately. Therefore, it is very essential to strengthen mental health and spiritual survival during the COVID-19 pandemic.